Introducing and Implementing HIV Self-Testing in Côte d'Ivoire, Mali, and Senegal: What Can We Learn From ATLAS Project Activity Reports in the Context of the COVID-19 Crisis? - Kra, Arsène Kouassi; Colin, Géraldine; Diop, Papa Moussa; Fotso, Arlette Simo; Rouveau, Nicolas; Hervé, Kouakou Kouamé; Geoffroy, Olivier; Diallo, Bakary; Kabemba, Odé Kanku; Dieng, Baidy; Diallo, Sanata; Vautier, Anthony; et al. (Frontiers in Public Health, 2021)
Background: The ATLAS program promotes and implements HIVST in Côte d'Ivoire, Mali, and Senegal. Priority groups include members of key populations—female sex workers (FSW), men having sex with men (MSM), and people who use drugs (PWUD)—and their partners and relatives. HIVST distribution activities, which began in mid-2019, were impacted in early 2020 by the COVID-19 pandemic. Methods: This article, focusing only on outreach activities among key populations, analyzes quantitative, and qualitative program data collected during implementation to examine temporal trends in HIVST distribution and their evolution in the context of the COVID-19 health crisis. Specifically, we investigated the impact on, the adaptation of and the disruption of field activities. Results: In all three countries, the pre-COVID-19 period was marked by a gradual increase in HIVST distribution. The period corresponding to the initial emergency response (March-May 2020) witnessed an important disruption of activities: a total suspension in Senegal, a significant decline in Côte d'Ivoire, and a less pronounced decrease in Mali. Secondary distribution was also negatively impacted. Peer educators showed resilience and adapted by relocating from public to private areas, reducing group sizes, moving night activities to the daytime, increasing the use of social networks, integrating hygiene measures, and promoting assisted HIVST as an alternative to conventional rapid testing. From June 2020 onward, with the routine management of the COVID-19 pandemic, a catch-up phenomenon was observed with the resumption of activities in Senegal, the opening of new distribution sites, a rebound in the number of distributed HIVST kits, a resurgence in larger group activities, and a rebound in the average number of distributed HIVST kits per primary contact. Conclusions: Although imperfect, the program data provide useful information to describe changes in the implementation of HIVST outreach activities over time. The impact of the COVID-19 pandemic on HIVST distribution among key populations was visible in the monthly activity reports. Focus groups and individual interviews allowed us to document the adaptations made by peer educators, with variations across countries and populations. These adaptations demonstrate the resilience and learning capacities of peer educators and key populations.